The Influence of Work Motivation and Career Development on Employee Loyalty, Case Study of PT Delta Indonesia Pranenggar - R. Hario Sulistianto; Fahri Haikal; Agung Priyono; Musdalifa Ramdhani Johardi (Komunitas Dosen Indonesia, 2024)
This study dives into the qualities companies seek in their workforce, highlighting the need for employees who are not only skilled but also dedicated to their tasks. By examining PT Delta Indonesia Praneggar's employees, it focuses on how work motivation and career development influence employee loyalty. The research draws from a sample of 36 permanent employees who have worked for at least two years. Data was collected using questionnaires—distributed either online or offline—and secondary sources like company records and documentation. The findings reveal an interesting pattern. Work motivation alone does not have a notable impact on employee loyalty. In contrast, career development significantly strengthens employee commitment. When examined together, work motivation and career development both contribute to fostering loyalty among employees. This indicates that while motivation is important, structured career growth plays a more substantial role in retaining a committed workforce.